Semantic Changes of Words in Albanian Language - Sula, Adelina (European Journal of Multidisciplinary Studies, 2016)
The language has changed over the years due to social, cultural, economic and scientific developments. Changes are not only in new words, but also in the same words with different meanings. These words are explained differently in dictionaries. In the language of politics, emphasis is a fruitful discourse strategy. Persuasion and convincing are key strategies of politics. In this paper, we study these words, reasons of changes. This study is based in the dictionaries of Albanian language. Comparing the dictionaries of 1980 to 2006 word by word, we highlight those words with different explanation.